Polyneuropathy and noncompressive cauda equina syndrome as manifestation of systemic lupus erythematosus : a case report - Ahmad Tirmizi, Jobli; Sharifah Aishah, Wan; Cheng Lay, Teh; Yaw Kiet, Cheong; Cindy Kueh, Hui San (BioMed Central Ltd., 2025)
Background Neuropsychiatric systemic lupus erythematosus covers a wide range of central nervous system and peripheral nervous system conditions. We report a rare case of a man with progressive muscle weakness and cauda equina syndrome. Case presentation A 32-year-old man of Chinese ethnicity presented with a 2-month history of progressive muscle weakness of the upper and lower limbs, associated with inflammatory joint pains, and rashes over the upper and lower limbs. Examination showed post-inflammatory hyperpigmentation over the upper and lower limbs and weakness in the proximal muscles of the upper and lower limbs. Laboratory investigations showed anemia, leukopenia, lymphopenia, positive antinuclear antibodies, positive anti-double-stranded deoxyribonucleic acid antibodies, positive anti-Smith antibodies, and positive anti-ribosomal P protein antibodies. He later developed acute urinary incontinence and weak anal tone. Magnetic resonance imaging of the spine showed leptomeningeal enhancement of the cauda equina. He was diagnosed with neuropsychiatric lupus with peripheral polyneuropathy and cauda equina syndrome. His condition was complicated with an infection and pulmonary embolism, but he eventually recovered with treatment. He was treated with high-dose steroids, hydroxychloroquine, intravenous immunoglobulin, anticoagulation, cyclophosphamide, and subsequently, mycophenolate mofetil. Conclusion This case highlights the rarity of peripheral neuropathy and noncompressive cauda equina syndrome in systemic lupus erythematosus. A collaborative effort by clinicians in multiple fields is required to achieve a diagnosis and satisfactory treatment in this patient.